Correction of Food Hypersensitivity as the Main Principle of Immunodietology in the Treatment of Obesity and Metabolic Disorders - P. S. Novikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
It can be assumed that the reason of failure of classical methods to combat obesity lies in the complete disregard of active involvement of the immune system in the processes of digestion, considering influence of food antigenic load, that  is carried by the human body. The new technology Immunodietology™, based on a mathematically correct calculation of the individual response of the body’s immune system to food antigens, is a promising trend for modern dietetics in addressing issues of prevention and control of obesity.Aim. To study the features of hypersensitivity to food antigens, as the main trigger of chronic inflammation in the development of obesity and metabolic disorders, to substantiate the personified principles of immunodietology application.Methods. The study of food hypersensitivity was carried out according to the methodology of Immunohealth™. Enzymelinked immunosorbent assay (ELISA) was used for specific IgG to 111 food antigens, distributed over antigenic clusters, to create an individual adaptation diet, based on the mathematically-based criterion “norm – anomaly”. We determined IL-4, IL-6, IL-10, IL-17, TSH, free T3, insulin in serum by means of ELISA.Results. A correlation was established between casein hypersensitivity and an increase in IL-6 concentrations (Rs = 0.30 (p < 0.05)); IL-17 (Rs = 0.32 (p < 0.05)), as well as food hypersensitivity (Type III) to casein and the development of atherogenic changes (OR = 2.7 (1.2; 6.3)).Conclusions. Thus, the results showed that the principles of diagnosis and evaluation, personalized food hypersensitivity are the basis of the new Immunodietology™ technology, which may be a promising trend in modern dietetics to control obesity.